KRAS and NRAS pyrosequencing screening in Tunisian colorectal cancer patients in 2015. Issue 3 (March 2019) - Jouini, Raja; Ferchichi, Marwa; BenBrahim, Ehsen; Ayari, Imen; Khanchel, Fatma; Koubaa, Wafa; Saidi, Olfa; Allani, Riadh; Chadli-Debbiche, Aschraf
Abstract: Background: Mutations in KRAS and NRAS often result in constitutive activation of RAS in the epidermal growth factor receptor (EGFR) signaling pathway. Mutations in KRAS exon 2 (codon 12–13) predict resistance to anti-EGFR targeted therapy in patients with metastatic colorectal carcinoma (mCRC). However, it's currently known that a significant proportion of mCRC have RAS mutations outside KRAS exon 2, particularly in exons 3 and 4 of KRAS and exons 2, 3 and 4 of NRAS. No data about RAS mutations outside KRAS exon 2 are available for Tunisian mCRC. The aim of this study was to analyze RAS, using pyrosequencing, in nine hotspots mutations in Tunisian patients with mCRC. Methods: A series of 131 mCRC was enrolled. Nine hotspots sites mutations of KRAS and NRAS were analyzed (KRAS: codons 12–13, codons 59–61, codon 117 and codon 146, NRAS: codons 12–13, codon 59, codon 61, codon 117 and codon 146) using Therascreen KRAS and RAS extension pyrosequencing kits. Results: Analysis was successful in 129 cases (98.5%). Mutations were observed in 97 cases (75.2%) dominated by those in KRAS exon 2 (86.6%). KRAS G12V was the most dominated mutation, observed in 25 cases (25.8%), and followed by KRAS G12S and KRAS G12D, each in 17 cases (17.5%). Mutations outside of KRAS exon 2 presented 13.4% of mutated cases and almost a third (28.8%) of KRAS exon 2 wild type mCRC. Among those, 9 cases (69.3%) carried mutations in NRAS exons 2, 3 and 4 and 4 cases (30.7%) in KRAS exons 3 and 4. Conclusions: RAS mutations outside exon 2 of KRAS should be included in routine practice, since they predict also response to anti-EGFR. That would make certain these patients benefit from appropriate testing and treatment. In addition unjustified expenses of anti-EGFR targeted therapy could be avoided.